CHARACTER EDUCATION STRATEGIES OF ISLAMIC BOARDING SCHOOLS IN INSTILLING RELIGIOUS MODERNIZATION VALUES - Siti Aisyatul Arifah (International Conference on Humanity Education and Society (ICHES), 2023)
Modernization or changes that occur in the world are certain and periodic. Therefore we need a strategy to deal with more modern changes in the world. This strategy can be made by anyone and any group, including pesantren. Islamic boarding school is the first education in Indonesia. Even though they are the oldest, Islamic boarding schools still exist, and are even being increasingly interested in by the millennial generation. Even so, it is a challenge for Islamic boarding schools to maintain the value of Islamic boarding school education and keep track of the currents of modernization without having to mix or even eliminate the value of Islamic boarding school education. This study aims first, to understand the strategy and contribution of pesantren to the modernization of religion. Second, to understand the relationship between pesantren education and religious modernization. Third, to understand the challenges and efforts faced by pesantren in strengthening the values ​​of religious modernization. This research method applies a descriptive qualitative approach. The type of research used is a case study. The form of research used is field research. The technique used in collecting this data was in the form of free interview techniques, participatory observation, and documentation with the caregivers of the Al – Anwar Bondowoso Islamic boarding school. To test the relevance of the data used in this study, source triangulation and technique triangulation were used. The results of this study indicate that Islamic boarding schools will at any time remain a vehicle or glue in instilling character values, especially characters that can be synergized with the values ​​of religious modernization, through their strategies and contributions in facing the challenges and efforts of Islamic boarding schools towards modernizing religion.